The Prospect of Solar Energy in the Development of Power Stations in the State of Kuwait - Ramadhan, Mohammad; Hussain, Abdulhameed; Behbehani, Dina (Journal of Renewable Energy, 2013)
Over the years, the production capacity for power generation has not been able to keep pace with the surge in electricity demand in the oil-rich State of Kuwait. To expand its power generation capacity, Kuwait's strategic energy plans focus on constructing gas turbine and fuel oil stations. This paper aimed to evaluate the prospect of photovoltaic solar energy (PV) in generating electricity as an alternative to decrease dependency on combined cycle gas turbine (CCGT) power stations. It applies the LCOE framework to evaluate the economic feasibility of installing a 100 MW PV and CCGT power stations in Kuwait. The results indicate that under the assumption of 5% interest rate, the estimated LCOE of PV station ($0.19/kWh) is unfeasible in comparison to the generation cost of gas turbine station ($0.11/kWh). However, the analysis has emphasized that evaluation of future electricity generation plans must not be limited to the LCOE criteria and should incorporate the following factors: the effect of natural gas supply constraints on the production of gas turbine plants, the environmental concerns of CO2 emissions, the peak load demand, and the domestic energy balance mix. The paper concludes that once these factors are addressed properly, the prospect of PV power stations becomes relatively feasible.